Svāmī Śraddhānanda : amara-śahīda Svāmī Śraddhānanda Jī Mahārāja kī pūrṇa, prāmāṇika, aura vistr̥ta jīvanī - Vidyālaṅkāra, Satyadeva, 1898-1965 (Vijaya-Pustaka-Bhaṇḍāra, 1933)
Life and work of Swami Sraddhananda, 1857-1926, Arya Samaj leader and a nationalist.